Survival and early neurodevelopmental outcomes in infants born at extreme prematurity in a tertiary neonatal centre in Hong Kong - Tania Wan; Naomi Wing-tung Wong; Winnie Wan-yee Tso; Mabel Siu-chun Wong (Elsevier, 2023)
We report the first study conducted in Hong Kong looking at survival and neurodevelopmental outcomes of extremely preterm infants (EPI), which includes information on primary school entry. Survival rate to discharge in our single centre cohort was 65.9%. Surviving EPIs were at risk of developmental delay (48.4%), as well as psychiatric and behavioural disorders, necessitating referral to special education services. Nevertheless, the vast majority (90.2%) of EPIs in our cohort are able to attend mainstream primary schools.